Stroke awareness in Brazil: what information about stroke is essential? - Octávio Marques Pontes‐Neto (2014)
Departamento de Neurociencias eCiencias do Comportamento,Faculdade de Medicina de RibeiraoPreto, Universidade de Sao Paulo,Ribeirao Preto SP, Brazil.Correspondence:Octavio Marques Pontes-Neto,Hospital das Clinicas, Faculdade deMedicina de Ribeirao Preto;Av. dos Bandeirantes, 3.900 / 4°andar / sala 438; 14049-900Riberao Preto SP, Brasil;E-mail: opontesneto@fmrp.usp.brConflict of interest:The author is currently the Presidentof the Brazilian Stroke Network, anon-governmental organization(NGO) devoted to promote andimprove global care of strokepatients throughout the country anddirectly involved on the organizationof stroke awareness campaigns inBrazil around the “World StrokeDay”. No financial incentives of anysort come from this position.Received 23 September 2014Accepted 30 September 2014